2020
DOI: 10.56093/ijans.v90i4.104178
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of protozoan parasitic infections in domestic dogs in Andhra Pradesh, India

Abstract: Faecal (2,250) and blood samples (1,350) of dogs received from Teaching Veterinary Clinical Complex (TVCC), Gannavaram, Veterinary Hospitals in and around Krishna district and nearby Krishna, Andhra Pradesh during last five years (January 2014 to December 2018) were examined to determine the prevalence of protozoan parasites. Faecal samples were analyzed by direct smear and floatation technique and blood samples after Giemsa's staining. The overall prevalence of protozoan parasitic infections including intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In studying prevalence of gastrointestinal endoparasites, the current study reveals that in line with those by Sreedhar et al (2009) who determine the prevalence of GIT gastrointestinal parasites as 42.0%. Muraleedharan et al (2005), Singh et al (2012), Rahman et al (2012) also reported the prevalence of endoparasites as 40.20%, 39.8% and 40.84% respectively which are close to the finding of present study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In studying prevalence of gastrointestinal endoparasites, the current study reveals that in line with those by Sreedhar et al (2009) who determine the prevalence of GIT gastrointestinal parasites as 42.0%. Muraleedharan et al (2005), Singh et al (2012), Rahman et al (2012) also reported the prevalence of endoparasites as 40.20%, 39.8% and 40.84% respectively which are close to the finding of present study.…”
Section: Discussionsupporting
confidence: 84%
“…In the current determination the large pervasiveness rate was found in winter season which is 41.53% followed by summer with 38.84% endoparasitic prevalance which is not in line with the study of Wadhwa et al(2011) ho has determined 73.9 % in winter followed by 52.8 % in summer. Seasonal occurrence and prevalence rate of parasitic infections reported by Sreedhar et al(2009), Muraleedharan et al(2005), Singh et al(2012 and Rahman et al (2012)are that the parasitic infestations are high in moosoon and low in winter which are not in line with the current study which shows high prevalence in winter followed by summer and moon soon.…”
Section: Discussioncontrasting
confidence: 62%
“…Jagannath [12] reported 36.25% gastrointestinal helminth infection in cattle and 42.12% in buffaloes. Choubisa and Jaroli [13] from Rajasthan reported 71.32% prevalence of gastrointestinal parasitic infection in diverse species of domestic ruminants, which is relatively higher than (39.34-67.24 %) reported from Andhra Pradesh [14], Jammu and Kashmir [15,16] and Maharashtra [17] states. Khan [18] reported an overall prevalence of 58.59%, with cows at 55.61% and buffaloes at 63.55%.…”
Section: Resultsmentioning
confidence: 94%